2016
DOI: 10.1371/journal.pone.0151433
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase Potentiates Glucocorticoid-Induced Osteonecrosis in a Mouse Model

Abstract: Osteonecrosis is a common dose-limiting toxicity of glucocorticoids. Data from clinical trials suggest that other medications can increase the risk of glucocorticoid-induced osteonecrosis. Here we utilized a mouse model to study the effect of asparaginase treatment on dexamethasone-induced osteonecrosis. Mice receiving asparaginase along with dexamethasone had a higher rate of osteonecrosis than those receiving only dexamethasone after 6 weeks of treatment (44% vs. 10%, P = 0.006). Similarly, epiphyseal arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 36 publications
11
64
0
Order By: Relevance
“…There was no difference in body weight of mice prior to placement on treatment (Supporting Information Figure S1). Both control and LPS‐only mice gained more weight than dexamethasone‐treated mice, consistent with our prior findings dexamethasone‐treated mice weigh less than control‐treated mice in this model . Dexamethasone plus LPS mice showed a transient delay, but not decrease, in weight gain compared with dexamethasone‐only mice (Figure A).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…There was no difference in body weight of mice prior to placement on treatment (Supporting Information Figure S1). Both control and LPS‐only mice gained more weight than dexamethasone‐treated mice, consistent with our prior findings dexamethasone‐treated mice weigh less than control‐treated mice in this model . Dexamethasone plus LPS mice showed a transient delay, but not decrease, in weight gain compared with dexamethasone‐only mice (Figure A).…”
Section: Resultssupporting
confidence: 90%
“…The severity of both osteonecrosis and arteriopathy was higher in mice treated with LPS (Figure ). These findings are consistent with our prior work, showing that proximal vasculature damage (e.g., arteriopathy) is the likely preceding and possibly causative event prior to development of osteonecrosis following dexamethasone with or without concurrent asparaginase . LPS has been shown to cause apoptosis of vascular endothelial cells and inhibition of vascular repair .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported that steroid caused significant enlargement of the adipocyte size and fat accumulation in the bone marrow, which contributes to the onset and progress of ONFH 20, 21. To investigate the role of HGE in repairing osteocytes damage, we performed steroid-induced ONFH rat model, which resulted in a significant osteonecrosis and extensive fat accumulation in the bone marrow, and allowed the rats to be recovered under the conditions with or without HGE treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, female sex is mentioned as an important determinant in most studies, especially in women of pubertal age [14]. Other anticancer agents such as methotrexate, as well as the combination of both asparaginase and corticosteroids, are suggested to be associated with osteonecrosis [3,11,14]. In addition, variability in the coagulation process is an important mechanism in the pathogenesis of osteonecrosis [1,12].…”
Section: Determinants Of Osteonecrosis In Pediatric Acute Lymphoblastmentioning
confidence: 99%